MPPT Control System Based on Incremental Conductance and Constant Voltage using Coupled Inductor-Capacitor Zeta Converter in hybrid PV-Wind Turbine System - Soedibyo Soedibyo; Mohammad Ridwan; Gusti Rinaldi Zulkarnain; Andri Pradipta; Sjamsjul Anam; Mochamad Ashari (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
This paper proposes a method of maximum power point tracking control using Incremental Conductance employed in hybrid photovoltaic-wind turbine for DC micro-grid system. The rapid growth of renewable energy using photovoltaic (PV) and wind turbine due to low operational cost and easy to implementation. Improvement of the efficiency of PV and wind turbine based on incremental conductance is the solution to get maximum power in PV and Wind Turbine. The proposed method uses variable step to achieve maximum power with high speed tracking, high efficiency and low steady state error calculation. The performance of the MPPT technique has been applied in dc-dc boost converter. Moreover, Zeta Converter using Coupled Inductor-Capacitor is added for maintain constant voltage in passive load. This high gain converter can reach 311 Volt DC with 1000 W output power and high efficiency up to 90%. The effectiveness of proposed method is implemented in two hybrid system using PV and wind turbine source. Keywords: incremental conductance technique; maximum power point tracking; Zeta Converter using Coupled Inductor-Capacitor.